2014
DOI: 10.1186/1471-244x-14-181
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to providing quality substance abuse treatment services for American Indian and Alaska native communities: perspectives of staff from 18 treatment centers

Abstract: BackgroundSubstance abuse continues to exact a significant toll, despite promising advancements in treatment, and American Indian and Alaska Native (AI/AN) communities remain disproportionately impacted. Understanding the challenges to providing quality substance abuse treatment to AI/AN communities could ultimately result in more effective treatment interventions, but no multi-site studies have examined this important issue.MethodsThis qualitative study examined the challenges of providing substance abuse tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Hartmann and Gone (2012) noted, "On one hand, many of these (urban) agencies wish to provide both standard Western and traditional healing services, but on the other hand, they lack concrete guidance for the design and integration of such services" (p. 543). Moreover, Legha et al (2014) pointed out that chemical dependency treatment programs for AI/ANs must deal with "pressure to use Evidence-Based Treatments (EBTs)" (p. 7). However, in a recent survey of chiefly rural substance abuse treatment programs for AI/ANs, Novins et al (2016) found that "only two of the commonly implemented psychosocial EBTs (Motivational Interviewing and Relapse Prevention Therapy) were endorsed as culturally appropriate by a majority of programs that had implemented them" (p. 214).…”
Section: Discussionmentioning
confidence: 99%
“…Hartmann and Gone (2012) noted, "On one hand, many of these (urban) agencies wish to provide both standard Western and traditional healing services, but on the other hand, they lack concrete guidance for the design and integration of such services" (p. 543). Moreover, Legha et al (2014) pointed out that chemical dependency treatment programs for AI/ANs must deal with "pressure to use Evidence-Based Treatments (EBTs)" (p. 7). However, in a recent survey of chiefly rural substance abuse treatment programs for AI/ANs, Novins et al (2016) found that "only two of the commonly implemented psychosocial EBTs (Motivational Interviewing and Relapse Prevention Therapy) were endorsed as culturally appropriate by a majority of programs that had implemented them" (p. 214).…”
Section: Discussionmentioning
confidence: 99%
“…These include challenges related to delivering clinical services (e.g., client trauma history and mistrust of service system, socioeconomic barriers faced by clients), limitations of the infrastructure of treatment settings (e.g., provider turnover, fatigue and burnout, lack of resources in the treatment setting), and the shortfalls of the greater service/treatment system (e.g., lack of sufficient aftercare resources, the employment of treatments inappropriate to the population). 41 Providers also express concern that many of the current evidence-based practices conflict with American Indian traditions and healing practices. 42…”
Section: Discussionmentioning
confidence: 99%
“…This project consisted of three phases: 1) convening an advisory board to identify key issues in the dissemination and implementation process and to develop study measures and methods (Novins et al, 2011), 2) completion of qualitative case studies of 18 substance abuse treatment programs serving AI/AN communities (Legha et al, 2014; Legha and Novins, 2012; Moore et al, 2015), and 3) conducting a national survey of AI/AN substance abuse treatment programs to explore their use of EBTs (Novins et al, 2012). This paper draws on the data collected during this final phase.…”
Section: Methodsmentioning
confidence: 99%